2021
DOI: 10.31803/tg-20210504112813
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis of Steel Welded Tubes Forming Process Using Numerical Simulations

Abstract: In this paper, the research results of the stability of steel welded tubes forming process are presented. The aim of this research is to determine influence of geometrical and tribological parameters on stability of the process and to determine optimal values of influential process parameters. A research plan with variation of influential parameters was made, on the basis of which experimental and numerical experiments were performed. Tube forming was performed in one operation in a two-part tool made of hard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Ge et al [10] established a model of hydraulic support and the environmental surface; they indicated that the simulation method is feasible for simulating the adaptive process. Meanwhile, the simulation method has been proven effective for technology optimization in different fields [11]. Hu [12] proposed a cooperative double closed-loop control technology to ensure secure contact between the roof and the canopy; they determined that canopy posture can be controlled well by using the proposed method.…”
Section: State Of the Artmentioning
confidence: 99%
“…Ge et al [10] established a model of hydraulic support and the environmental surface; they indicated that the simulation method is feasible for simulating the adaptive process. Meanwhile, the simulation method has been proven effective for technology optimization in different fields [11]. Hu [12] proposed a cooperative double closed-loop control technology to ensure secure contact between the roof and the canopy; they determined that canopy posture can be controlled well by using the proposed method.…”
Section: State Of the Artmentioning
confidence: 99%